PENERAPAN TEKNOLOGI BUDIDAYA DAN KOMPONEN KAWASAN PENGEMBANGAN SAPI POTONG DI KABUPATEN RAJA AMPAT - Mochammad Said Soltief; Asnath M Fuah; Rudy Priyanto (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
The aims of this study were to determine the application of livestock breeding technology and the specific components in order to develop strategic planning for cattle production in Raja Ampat district. A total of 218 farmer from three different villages, namely Sakabu, Kalobo, and Waijan were observed and intervewied.The land and their use system, a pattern of cattle management production, and the characteristic of institutional and government regulation were observed as study variables. These three major variables were divided to collect the comprehensive data. The second variables covered reproduction, maintenance and housing, feed, disease and health, assistance, facilities and infrastructure, postharvest handling, and marketing. The third consist of farmer organization and capital resources and regional support system to enhance cattle production.The results showed : (1) pastoral system was common where farmers allows their cattle to graze freely in various places such as grassland, forest, rice fields or farmland, (2) the selective breeding practice was unadopted instead of the traditional mating, and (3) application of feeding technology not applied properly.Raja Ampat, a center of cattle breeding and fattening, was identified as a new prospective development area based on total score (< 500).